Characterization of PYL gene family and identification of HaPYL genes response to drought and salt stress in sunflower - Zhaoping Wang; Jiayan Zhou; Jian Zou; Jun Yang; Weiying Chen (PeerJ, 2024)
In the context of global climate change, drought and soil salinity are some of the most devastating abiotic stresses affecting agriculture today. PYL proteins are essential components of abscisic acid (ABA) signaling and play critical roles in responding to abiotic stressors, including drought and salt stress. Although PYL genes have been studied in many species, their roles in responding to abiotic stress are still unclear in the sunflower. In this study, 19 HaPYL genes, distributed on 15 of 17 chromosomes, were identified in the sunflower. Fragment duplication is the main cause of the expansion of PYL genes in the sunflower genome. Based on phylogenetic analysis, HaPYL genes were divided into three subfamilies. Members in the same subfamily share similar protein motifs and gene exon-intron structures, except for the second subfamily. Tissue expression patterns suggested that HaPYLs serve different functions when responding to developmental and environmental signals in the sunflower. Exogenous ABA treatment showed that most HaPYLs respond to an increase in the ABA level. Among these HaPYLs, HaPYL2a, HaPYL4d, HaPYL4g, HaPYL8a, HaPYL8b, HaPYL8c, HaPYL9b, and HaPYL9c were up-regulated with PEG6000 treatment and NaCl treatment. This indicates that they may play a role in resisting drought and salt stress in the sunflower by mediating ABA signaling. Our findings provide some clues to further explore the functions of PYL genes in the sunflower, especially with regards to drought and salt stress resistance.